Cost of seeking care for tuberculosis since the implementation of universal health coverage in Indonesia - Ahmad Fuady; Tanja A. J. Houweling; Muchtaruddin Mansyur; Erlina Burhan; Jan Hendrik Richardus (BMC, 2020)
Abstract Background Although tuberculosis (TB) patients often incur high costs to access TB-related services, it was unclear beforehand whether the implementation of universal health coverage (UHC) in Indonesia in 2014 would reduce direct costs and change the pattern of care-seeking behaviour. After its introduction, we therefore assessed TB patients' care-seeking behaviour and the costs they incurred for diagnosis, and the determinants of both. Methods In this cross sectional study, we interviewed adult TB patients in urban, suburban, and rural districts of Indonesia in July-September 2016. We selected consecutively patients who had been treated for TB in primary health centers for at least 1 month until we reached at least 90 patients in each district. After establishing which direct and indirect costs they had incurred during the pre-diagnostic phase, we calculated the total costs (in US Dollars). To identify the determinants of these costs, we applied a general linear mixed model to adjust for our cluster-sampling design. Results Ninety-three patients of the 282 included in our analysis (33%) first sought care at a private clinic. The preference for such clinics was higher among those living in the rural district (aOR 1.88, 95% CI 0.85-4.15, P = 0.119) and among those with a low educational level (aOR 1.69, 95% CI 0.92-3.10, P = 0.090). Visiting a private clinic as the first contact also led to more visits (β 0.90, 95% CI 0.57-1.24, P < 0.001) and higher costs than first visiting a Primary Health Centre, both in terms of direct costs (β = 16.87, 95%CI 10.54-23.20, P < 0.001) and total costs (β = 18.41, 95%CI 10.35-26.47, P < 0.001). Conclusion Despite UHC, high costs of TB seeking care remain, with direct medical costs contributing most to the total costs. First seeking care from private providers tends to lead to more pre-diagnostic visits and higher costs. To reduce diagnostic delays and minimize patients' costs, it is essential to strengthen the public-private mix and reduce the fragmented system between the national health insurance scheme and the National TB Programme.